Exogenous Vitamin D3 Modulates Response of Bovine Macrophages to Mycobacterium avium subsp. paratuberculosis Infection and Is Dependent Upon Stage of Johne’s Disease - Wherry, Taylor L. T.; Dassanayake, Rohana P.; Casas, Eduardo; Mooyottu, Shankumar; Bannantine, John P.; Stabel, Judith R. (Frontiers in Cellular and Infection Microbiology, 2022)
Mycobacterium avium subspecies paratuberculosis (MAP), the causative agent of ruminant enteritis, targets intestinal macrophages. During infection, macrophages contribute to mucosal inflammation and development of granulomas in the small intestine which worsens as disease progression occurs. Vitamin D3 is an immunomodulatory steroid hormone with beneficial roles in host-pathogen interactions. Few studies have investigated immunologic roles of 25-hydroxyvitamin D3 (25(OH)D3) and 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) in cattle, particularly cattle infected with MAP. This study examined the effects of exogenous vitamin D3 on immune responses of monocyte derived macrophages (MDMs) isolated from dairy cattle naturally infected with MAP. MDMs were pre-treated with  100 ng/ml 25(OH)D3 or  4 ng/ml 1,25(OH)2D3, then incubated 24 hrs with live MAP in the presence of their respective pre-treatment concentrations. Following treatment with either vitamin D3 analog, phagocytosis of MAP by MDMs was significantly greater in clinically infected animals, with a greater amount of live and dead bacteria. Clinical cows had significantly less CD40 surface expression on MDMs compared to subclinical cows and noninfected controls. 1,25(OH)2D3 also significantly increased nitrite production in MAP infected cows. 1,25(OH)2D3 treatment played a key role in upregulating secretion of pro-inflammatory cytokines IL-1 and IL-12 while downregulating IL-10, IL-6, and IFN-. 1,25(OH)2D3 also negatively regulated transcripts of CYP24A1, CYP27B1, DEFB7, NOS2, and IL10. Results from this study demonstrate that vitamin D3 compounds, but mainly 1,25(OH)2D3, modulate both pro- and anti-inflammatory immune responses in dairy cattle infected with MAP, impacting the bacterial viability within the macrophage.